Strategi Pengelolaan SDM untuk menghadapi Tantangan Pasar Global Pada Industri Konveksi Tas (Studi Kasus: Konveksi Tas Baraya Sadaya, Kabupaten Bandung) - Nuraeni, Yuni Siti; Maryono, Dicky (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This research is motivated by the discovery of a problem, namely the lack of effective human resource (HR) management in facing global market challenges in the bag convection industry, especially at Konveksi Tas Baraya Sadaya. Many companies have difficulty optimizing the potential of their workforce to increase competitiveness and productivity in the international market. This study aims to analyze the HR management strategy implemented by Konveksi Tas Baraya Sadaya in facing global market competition and identify factors that influence the company's competitiveness in the bag convection industry. This study departs from a theory that effective HR management can improve employee technical skills, reduce turnover rates, and create deep loyalty, which in turn will contribute to the company's competitiveness in facing global market challenges. This study uses a qualitative approach with data collection through interviews, direct observation, and document review. The data analysis method is carried out with credibility, transferability, dependability, and confirmability. Based on the results of data analysis, it was concluded that HR management focused on developing technical skills and employee loyalty, without involving formal recruitment from outside the company, has proven effective in increasing the competitiveness of Konveksi Tas Baraya Sadaya in the global market. Trained technical skills and high commitment from employees are key factors in maintaining product quality and innovation needed to remain competitive